Experimental investigation of efficiency of square flat-plate solar collector using SiO2/water nanofluid. (September 2016) - Noghrehabadi, Aminreza; Hajidavalloo, Ebrahim; Moravej, Mojtaba
Abstract: In the present study, a SiO2 /water nanofluid with a mass fraction of 1% was employed as a coolant, and its the effect on the performance of a symmetric, square flat-plate solar collector was experimentally investigated. The experiments were performed under the ASHRAE standard without any surfactants. The effect of the nanofluid on the collector efficiency was examined with respect to the solar radiation, mass flow rate, and temperature variation. The results indicate that compared with pure water, the SiO2 /water nanofluid enhanced the thermal efficiency and temperature performance. Moreover, the collector was more efficient with the nanofluid than with water owing to the solar radiation and mass flow rate.